Reviews (Blackfriars, 1922)
Reviews in this Article Treasury of Indulgences. By M. P. Donelan. The Popes in the Divina Commedia of Dante. By L. C. Casartelli, Bishop of Salford. Singing Beads: Woodcuts and Verses. By Dom Theodore Baily, O.S.B. A History of Sinai. By Lina Eckenstein.